Perawatan Teknik Begg Pada Maloklusi Klas I Dengan Kaninus Impaksi dan Insisivus Lateral Agenesis - Kristina Wijaya Gunawan; Wayan Ardhana; Christnawati Christnawati (Faculty of Dentistry, Universitas Gadjah Mada, 2013)
Impaksi kaninus maksila sering dijumpai pada sisi palatal daripada labial. Agenesis adalah anomali pertumbuhan akibat tidak ada satu atau lebih benih gigi. Laporan kasus ini bertujuan memaparkan kemajuan perawatan kasus Maloklusi klas I dengan kaninus impaksi dan insisivus lateral agenesis menggunakan alat cekat teknik Begg. Seorang pasien usia 20 tahun datang mengeluhkan gigi-gigi depan atas dan bawah yang berjejal sehingga mengganggu penampilan. Perawatan bertujuan untuk koreksi Maloklusi Angle klas I tipe dentoskeletal dengan deepbite, crossbite gigi 25 terhadap 35, pergeseran midline dental maksila dan mandibula ke kanan sebesar 2,5 mm dan 3,0 mm, 13 impaksi vertikal pada sisi labial, 42 agenesis, dan edentulous parsial regio 36. Koreksi dilakukan dengan pencabutan 14, 25, pemanfaatan ruang bekas pencabutan 36 dan exposure gigi kaninus yang impaksi. Tahap pertama teknik Begg adalah leveling, unraveling, dan bite opening, diikuti dengan koreksi midline dan penutupan sisa ruang bekas pencabutan. Kesimpulan: perawataan ortodontik menggunakan teknik Begg yang dilakukan simultan dengan exposure kaninus impaksi labial dengan closed eruption technique dapat memberikan hasil yang memuaskan.Treatment for Class I Malocclusion with Impacted Canine and Agenesis Lateral Incisor Using Begg Technique. Maxillary canine impaction occurs commonly on the palatal than labial side. Agenesis is a developmental anomaly condition because of the absence of one or more tooth buds. This case report aims to explain the treatment progress of class I malocclusion with impacted canine and agenesis lateral incisor using fixed appliance through Begg technique. A 20-year-old female patient complained about her upper and lower anterior dental crowding that disturbed her appearance. The treatment aims to correct the Angle class I malocclusion dentoskeletal types with deepbite, crossbite 25 to 35, maxillary and mandibulary dental midline shift to the right by 2.5 mm and 3.0 mm, 13 labially vertical impacted, 42 agenesis, and partial edentulous 36. The correction was obtained through extraction 14 and 25, and the use of former space from extraction 36 and exposure of impacted canine. The first step of treatment using Begg technique is to leveling, unraveling, and bite opening. The second step is midline correction and space closure. Finally, it can be concluded that orthodontic treatment using Begg technique which is done simultaneously and exposure of labial- canine impaction with closed eruption technique can give satisfactory results.